An Evaluation of Critical Reading Materials at English Language Department of Universitas Negeri Padang - Fajar Sukmana; Fitrawati Fitrawati (Universitas Negeri Padang, 2021)
To develop a good material, materials developer needs to evaluate the previous materials being used by using the criteria of good materials. This study aims to evaluate the critical reading materials at English Language Department of Universitas Negeri Padang based on Cunningsworth checklist. This research was a descriptive study using a quantitative approach with the instrument of data collection technique using a questionnaire. The respondents in this study were four lecturers of English Language Department of Universitas Negeri Padang who had ever experienced in teaching critical reading course. They were given 50 questions to evaluate the teaching materials in critical reading course. The results showed that Aims and Approaches was categorized as “Fair” (64%), Design and Organization was categorized as “Sufficient” (59%), Language Content was categorized as “Fair” (72%), Skills was categorized as “Fair” (71%), Topics was categorized as “Fair” (63%), Methodology was categorized as “Sufficient” (58%), and Practical Considerations was categorized as “Fair” (60%). Overall, the quality of this material was categorized as “Fair” with the total was 64%. It still needs improvements in several aspects for example: The coverage of the materials based on what is needed, the usage of different teaching and learning styles, the made up components of materials package, the organization of the materials (according to the structures, functions, topics, and skills).